Pengaruh Debt to Equity Ratio (DER), Total Asset Turnover (TATO), dan Net Profit Margin (NPM) terhadap Pertumbuhan Laba pada Sub Sektor Kimia yang Terdaftar di Bursa Efek Indonesia - Siti Nur Dilla; Hadi Suriono (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study investigates the effect of Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Net Profit Margin (NPM) on profit growth in chemical sub-sector companies listed on the Indonesia Stock Exchange. The research was motivated by fluctuations in company profit growth despite changes in financial performance indicators. This study employed a quantitative approach using secondary data obtained from annual financial reports during the 2022–2024 period. The sample consisted of 11 companies selected through purposive sampling, resulting in 33 observations. Data were analyzed using multiple linear regression with the assistance of SPSS version 22 after passing the classical assumption tests. The results show that DER, TATO, and NPM simultaneously have a significant effect on profit growth. Partially, DER does not have a significant effect on profit growth, while TATO has a positive and significant effect on profit growth. Meanwhile, NPM shows a negative relationship with profit growth. The coefficient of determination indicates that the independent variables explain 34.2% of the variation in profit growth, while the remaining 65.8% is influenced by other factors outside the research model. The findings indicate that efficient asset management contributes to increasing company profit growth.